QscR, a LysR-Type Transcriptional Regulator and CbbR Homolog, Is Involved in Regulation of the Serine Cycle Genes in Methylobacterium extorquens AM1 - Kalyuzhnaya, Marina G. (American Society for Microbiology, 2003)
A new gene, qscR, encoding a LysR-type transcriptional regulator that is a homolog of CbbR, has been characterized from the facultative methylotroph Methylobacterium extorquens AM1 and shown to be the major regulator of the serine cycle, the specific C(1) assimilation pathway. The qscR mutant was shown to be unable to grow on C(1) compounds, and it lacked the activity of serine-glyoxylate aminotransferase, a key enzyme of the serine cycle. Activities of other serine cycle enzymes were decreased during growth on C(1) compounds compared to the activities found in wild-type M. extorquens AM1. Promoter fusion assays, as well as reverse transcription-PCR assays, have indicated that the serine cycle genes belong to three separate transcriptional units, sga-hpr-mtdA-fch, mtkA-mtkB-ppc-mcl, and gly. Gel retardation assays involving the purified QscR have demonstrated the specific binding of QscR to the DNA regions upstream of sga, mtkA, gly, and qscR. We conclude that QscR acts as a positive transcriptional regulator of most of the serine cycle enzymes and also as an autorepressor.